When clouds collide. (Economist, 2008)
The article discusses the bid by software company Microsoft Corp. to acquire Internet company Yahoo! in an effort to challenge the online advertising dominance of Google Inc., as well as become a stronger player in the area of "cloud computing." This refers to the move away from personal devices as the locus of computing and toward remote complexes or "clouds" of hardware and software that users access online.